Design and Development of a Portable Surveillance Robot with Wireless Control Using ESP32-CAM for Tactical Intelligence Purposes - Dwi Wahyu; Kasiyanto; Suko Wiyanto (CV Edujavare Publishing, 2026)
This research aims to design and develop a portable surveillance robot with wireless control using the ESP32-CAM module as an innovative solution to support tactical intelligence needs in high-risk environments. Through the prototype research method, this system is developed to facilitate real-time surveillance without requiring personnel to be directly present in dangerous locations, thereby minimizing risks to human safety. The robot integrates major components such as the ESP32-CAM as the main control center and video transmission medium, the L298N motor driver, and four DC motors that enable mobility across various urban and open-field terrains. Supported by a Li-ion battery power source, the device is capable of transmitting visual data efficiently through a Wi-Fi network to the control device, which is expected to improve operational effectiveness and decision-making accuracy in surveillance and security missions.